Asociación Mexicana de Hepatología A.C. Guía Clínica de Hepatitis B - Higuera de la Tijera, María de Fátima; Castro Narro, Graciela; Velarde Ruiz Velasco, José Antonio; Cerda Reyes, Eira; Moreno Alcántar, Rosalba; Aiza Haddad, Ignacio; Castillo Barradas, M.; Cisneros Garza, Laura Esthela; Dehesa Violante, Margarita; Flores Calderón, J.; González Huezo, M. S.; Márquez Guillén, E.; et al. (Asociación Mexicana de Gastroenterología, 2021)
Hepatitis B virus (HBV) infection continues to be a worldwide public health problem. In Mexico, at least three million adults are estimated to have acquired hepatitis B (total hepatitis B core antibody [anti-HBc]-positive), and of those, 300,000 active carriers (hepatitis B surface antigen [HBsAg]-positive) could require treatment. Because HBV is preventable through vaccination, its universal application should be emphasized. HBV infection is a major risk factor for developing hepatocellular carcinoma. Semi-annual liver ultrasound and serum alpha-fetoprotein testing favor early detection of that cancer and should be carried out in all patients with chronic HBV infection, regardless of the presence of advanced fibrosis or cirrhosis. Currently, nucleoside/nucleotide analogues that have a high barrier to resistance are the first-line therapies.